2003
DOI: 10.1002/hep.1840380414
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK mediates fibrogenic signal through smad3 phosphorylation in rat myofibroblasts

Abstract: Mikio Ni~hizawa,~ Hepatic stellate cells (HSCs) spontaneously transdifferentiate into myofibroblast (MFB) -phenotype on plastic dishes. This response recapitulates the features of activation in viva Transforming growth &tor P (TGF-P) plays a prominent role in stimulating liver fibrogenesis by MFBs. In quiescent HSCs, TGF-P signaling involves TGF-P type I receptor (TPRI)-mediated phosphorylation of serine residues within the conserved SSXS motif at the C-terminus of Smad2 and Smad3. The middle linker regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
164
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(170 citation statements)
references
References 27 publications
(2 reference statements)
5
164
1
Order By: Relevance
“…Western blot analysis of cell lysates using these antibodies revealed a time-dependent activation of Smad 2 and Smad 3 (Figure 5A), while there was no change in total Smad 2/3 level in ROS osteoblast-like cells. Recent studies have shown that Erk could modify the linker region at Seine 213 between the MH1 and MH2 domain of R-Smads (Furukawa et al, 2003; Kamaraju and Roberts, 2005; Kretzschmar et al, 1999; Matsuura et al, 2005; Wang et al, 2009a). Therefore, we determined the phosphorylation status of linker region of Smad 3 under different conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Western blot analysis of cell lysates using these antibodies revealed a time-dependent activation of Smad 2 and Smad 3 (Figure 5A), while there was no change in total Smad 2/3 level in ROS osteoblast-like cells. Recent studies have shown that Erk could modify the linker region at Seine 213 between the MH1 and MH2 domain of R-Smads (Furukawa et al, 2003; Kamaraju and Roberts, 2005; Kretzschmar et al, 1999; Matsuura et al, 2005; Wang et al, 2009a). Therefore, we determined the phosphorylation status of linker region of Smad 3 under different conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of p38 signaling has been demonstrated to attenuate fibrotic responses in vivo in experimental models of renal fibrosis [4851], cardiac fibrosis [52, 53], and in myofibroblast activation in vitro [5456]. Thus, our data demonstrating that p38 has the ability to not only potentiate FGF2-mediated inhibition of myofibroblast phenotypes, but also to inhibit TGFβ-mediated myofibroblast differentiation directly, add the suggestion of p38 inhibition as a potential treatment for dermal fibrosis to a growing body of literature suggesting the potential efficacy of p38 inhibition as antifibrotic therapy in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TGF-β regulates the transformation of human lung fibroblasts into myofibroblasts through MAPK signal transduction pathways, producing extracellular matrix proteins and resulting in lung interstitial fibrosis (50). Lu et al confirmed that Smad2 plays a role in pulmonary vascular endothelial permeability induced by TGF-β1; thus, increased TGF-β1 may promote lung injury (51).…”
Section: Discussionmentioning
confidence: 99%